INFLUENCE OF THE MODERN SYSTEMS OF THE BLAST STEEL-FURNACE ELECTRICAL PARAMETERS CONTROL ON CAPACITY AND TECHNICAL AND ECONOMICAL INDICES OF MELTING - D. N. Andrianov; V. N. Prohorenko; A. S. Zazjan (Литьë и металлургия, 2006)
The reduction of time under the current, electric energy rate, electrodes rate at working of arc steel-furnace with new transformer of capacity 95 MBA and with regulating system SIMELT-AC-NEC are noted.